A Mixed Cooperative Dual to the Nash Equilibrium. (15th September 2015) - Corley, H. W.
Abstract : A mixed dual to the Nash equilibrium is defined forn -person games in strategic form. In a Nash equilibrium every player's mixed strategy maximizes his own expected payoff for the othern - 1 players' strategies. Conversely, in the dual equilibrium everyn - 1 players have mixed strategies that maximize the remaining player's expected payoff. Hence this dual equilibrium models mutual support and cooperation to extend the Berge equilibrium from pure to mixed strategies. This dual equilibrium is compared and related to the mixed Nash equilibrium, and both topological and algebraic conditions are given for the existence of the dual. Computational issues are discussed, and it is shown that for eachn > 2 there exists a game for which no dual equilibrium exists.